Ten strategies for a successful transition to remote learning: Lessons learned with a flipped course - Ana E. Garcia‐Vedrenne; Chloé Orland; Kimberly M. Ballare; Beth Shapiro; Robert K. Wayne (Ecology and Evolution, 2020)
Abstract Transitioning from in‐person to remote learning can present challenges for both the instructional team and the students. Here, we use our course “Biodiversity in the Age of Humans” to describe how we adapted tools and strategies designed for a flipped classroom to a remote learning format. Using anonymous survey data collected from students who attended the course either in‐person (2019) or remotely (2020), we quantify student expectations and experiences and compare these between years. We summarize our experience and provide ten “tips” or recommendations for a transition to remote learning, which we divide into three categories: (a) precourse instructor preparation; (b) outside of class use of online materials; and (c) during class student engagement. The survey results indicated no negative impact on student learning during the remote course compared to in‐person instruction. We found that communicating with students and assessing specific needs, such as access to technology, and being flexible with the structure of the course, simplified the transition to remote instruction. We also found that short, pre‐recorded videos that introduce subject materials were among the most valuable elements for student learning. We hope that instructors of undergraduate ecology and evolution courses can use these recommendations to help establish inclusive online learning communities that empower students to acquire conceptual knowledge and develop scientific inquiry and literacy skills.